Oxidative dissolution of covellite by Thiobacillus ferrooxidans - Monteiro, V. F. [UNESP]; Garcia, O. [UNESP]; Tuovinen, O. H. (Elsevier, 1999)
Oxidation of research-grade covellite was investigated in respirometric and growth experiments with Thiobacillus ferrooxidans. Covellite was directly oxidized by T. ferrooxidans in respirometric experiments, but the pH of mineral salts medium increased to prohibitively high values because of high sulfide concentrations. In glycine-H 2SO 4 buffered medium the pH remained steady and the oxygen uptake activity of T. ferrooxidans was not inhibited. In cultures growing with covellite as the sole source of energy, the pH increased to about 4. Redox potential increased to 500-600 mV during bacterial oxidation of covellite in the presence and absence of additional Fe 2+, whereas it remained mostly at about 350 mV in abiotic control. Jarosite was a major solid-phase product in T. ferrooxidans cultures. The solubilization of copper from covellite in inoculated flasks was higher than that obtained in control flasks and was not enhanced in the presence of additional Fe 2+.The sample also contained bornite (Cu 5FeS 4) which released iron in solution under all experimental conditions. Accumulation of S 0 was apparent only in inoculated covellite samples. © 1997 Elsevier B.V. All rights reserved.